(untitled) (Research, Society and Development, 2020)
Quality in the provision of health services is an indispensable element for companies, as it seeks to maximize the well-being and satisfaction of the client. In this sense, the evaluation of this service becomes relevant because it allows identifying the weaknesses to be corrected. Thus, the study aims to assess the level of quality of care in a medical clinic in the city of Pau dos Ferros / RN through the application of the SERVQUAL model. This research is characterized as a descriptive, exploratory study, configured as a case study. The SERVQUAL model was used as a research tool, based on the application of 2 questionnaires consisting of 22 questions each, applied to 50 customers. As a result of the research, it was found that the main negative gaps identified are associated with tangibility and responsiveness, in which the absence of parking spaces and the time spent in queues stand out. However, the positive determinants stand out, being reliability, security and empathy. It is important to have a continuous process of monitoring, identifying the causes of the negative points found and adopting adequate mechanisms for improvement.